2017
DOI: 10.14348/molcells.2017.0088
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Striatal Circuits Underlying Addiction-Like Behaviors

Abstract: Drug addiction is a severe psychiatric disorder characterized by the compulsive pursuit of drugs of abuse despite potential adverse consequences. Although several decades of studies have revealed that psychostimulant use can result in extensive alterations of neural circuits and physiology, no effective therapeutic strategies or medicines for drug addiction currently exist. Changes in neuronal connectivity and regulation occurring after repeated drug exposure contribute to addiction-like behaviors in animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…The negative emotional stage of withdrawal may be due to activation of the amygdala with norepinephrine, dynorphin and corticotropin-releasing factor. The third stage, craving, depends on the prefrontal cortex, amygdala and hippocampus, and glutamate is the major neurotransmitter involved (reviewed in Kelley and Berridge, 2002 ; Koob and Volkow, 2010 ; Kim et al, 2017 ; Figure 1 ). The NAc acts as a hub of convergence from the different regions, and it has been considered a key element in the neuronal circuitry of drug addiction.…”
Section: Brain Circuitry and Adenosine Receptor Interactionsmentioning
confidence: 99%
“…The negative emotional stage of withdrawal may be due to activation of the amygdala with norepinephrine, dynorphin and corticotropin-releasing factor. The third stage, craving, depends on the prefrontal cortex, amygdala and hippocampus, and glutamate is the major neurotransmitter involved (reviewed in Kelley and Berridge, 2002 ; Koob and Volkow, 2010 ; Kim et al, 2017 ; Figure 1 ). The NAc acts as a hub of convergence from the different regions, and it has been considered a key element in the neuronal circuitry of drug addiction.…”
Section: Brain Circuitry and Adenosine Receptor Interactionsmentioning
confidence: 99%
“…Drug addiction is a severe mental illness characterized by compulsive drug abuse despite the potential undesirable consequences. Previous studies have indicated that the use of psychoactive stimulants may lead to changes in a wide range of neurological circuits and physiological processes ( 38 ). Psychostimulants play a significant role in promoting the structural plasticity of reward circuits in the brain ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal striatum is comprised of the caudate nucleus and putamen (CPu), and the ventral striatum of the nucleus accumbens (NAc) [8,24]. The CPu receives dopaminergic inputs from the substantia nigra pars compacta in the midbrain and glutamatergic inputs mainly from the somatosensory cortex [24,25]. On the other hand, the NAc receives dopaminergic inputs from the ventral tegmental area (VTA) in the midbrain and glutamatergic inputs from the prefrontal cortex (PFC) [25].…”
Section: The Striatum Potentiates Glutamate Release After Nicotinementioning
confidence: 99%